Responses of soil fungal community composition and function to wetland degradation in the Songnen Plain, northeastern China - Yan, Zhizhi; Yang, Shuhan; Chen, Lei; Zou, Yu; Zhao, Yupeng; Yan, Guang; Wang, He; Wu, Yining (Frontiers in Plant Science, 2024)
Wetlands are ecosystems that have a significant impact on ecological services and are essential for the environment. With the impacts of rapid population growth, wetland reclamation, urbanization, and land use change, wetlands have undergo severe degradation or loss. However, the response of soil fungal communities to wetland degradation remains unknown. To understand the variety and population of soil fungi in the Songnen Plain wetlands with varying degradation levels, we studied how soil fungi react to wetland degradation and progression. This research utilized highthroughput sequencing technology to analyze the variety and abundance of soil fungi in the undegraded (UD), light degraded (LD), moderate degraded (MD), and severe degraded (SD) conditions in the Halahai Nature Reserve of Songnen Plain. This study also explored how these fungi are related to the soil's physicochemical properties in wetlands at various degradation levels. The findings indicated that Basidiomycota and Ascomycota were the primary phyla in the Songnen Plain, with Ascomycota increasing and Basidiomycota decreasing as wetland degradation progressed. Significant differences were observed in soil organic carbon (SOC), total nitrogen (TN), and soil total potassium (TK) among the succession degradation stages. With the deterioration of the wetland, there was a pattern of the Shannon and Chao1 indices increasing and then decreasing. Non-metric Multidimensional Scaling (NMDS) analysis indicated that the fungal community structures of UD and LD were quite similar, whereas MD and SD exhibited more distinct differences in their fungal community compositions. Redundancy analysis (RDA) results indicated that Soil Water content (SWC) and total nitrogen (TN) were the primary environmental factors influencing the dominant fungal phylum. According to the FUNGuild prediction, Ectomycorrhizal and plant pathogenis gradually declining with wetland degradation. In general, our findings can offer theoretical support for the preservation and rehabilitation of damaged wetlands.